Strong Inhibitory Effect, Low Cytotoxicity and High Plasma Stability of Steroidal Inhibitors of N-Methyl-D-Aspartate Receptors With C-3 Amide Structural Motif - Adla, Santosh Kumar; Slavikova, Barbora; Chodounska, Hana; Vyklicky, Vojtech; Ladislav, Marek; Hubalkova, Pavla; Krausova, Barbora; Smejkalova, Tereza; Nekardova, Michaela; Smidkova, Marketa; Monincova, Lenka; Soucek, Radko; et al. (Frontiers in Pharmacology, 2018)
Herein, we report the synthesis, structure-activity relationship study, and biological evaluation of neurosteroid inhibitors of N-methyl-D-aspartate (NMDA) receptors that employ an amide structural motif, relative to pregnanolone glutamate (PAG) – a compound with neuroprotective properties. Our results demonstrate that all compounds were found to be more potent NMDA inhibitors (IC50 values varying from 1.4 to 21.7 µM) than PAG (IC50 = 51.7 µM). Selected compound 6 was evaluated for its NMDAR subtype selectivity and its ability to inhibit AMPAR/GABAR responses. Compound 6 inhibits the NMDA receptors (8.3 ± 2.1 µM) more strongly than it does at the GABA and AMPA receptors (17.0 ± 0.2 µM and 276.4 ± 178.7 µM, respectively). Next, compounds 3, 5-7, 9, and 10 were not associated with mitotoxicity, hepatotoxicity nor ROS induction. Lastly, we were able to show that all compounds have improved rat and human plasma stability over PAG.